A note on the anomalous tilt preceding the Koyna earthquake Of 10 December 1967 - RAO, P. SITAPATHI; BHATTACHARYYA , N.; RAO, B. RAMALINGESWARA (MAUSAM, 1979)
Employing the tiltgraph data of the Koyna Dam Observatory published in the reports of the Central Water and Power Research Station, Khadakwasla, Pune (1970), weekly mean value of the daily variation or the tits has been computed for a period of six months starting from November 1967 to March 1968 which covers the main shock of 10 December 1967 and its aftershocks. A plot of the weekly means on the time scale gives a systematic change in tilt and cloys finally (a high value of 1.2 micro radians in this case) preceding the earthquake. Further it abruptly reverses by 180° in its direction about two weeks prior to the major shock, which may be considered a precursor. The analysis and the results obtained thus are discussed for the 10 December 1967 earthquake and its aftershocks in the Koyna region.